Management of Parenteral Nutrition in Hospitalized Adult Patients. (1st September 2016) - Mundi, Manpreet S.; Nystrom, Erin M.; Hurley, Daniel L.; McMahon, M. Molly
Abstract : Despite the high prevalence of malnutrition in adult hospitalized patients, surveys continue to report that many clinicians are undertrained in clinical nutrition, making targeted nutrition education for clinicians essential for best patient care. Clinical practice models also continue to evolve, with more disciplines prescribing parenteral nutrition (PN) or managing the cases of patients who are receiving it, further adding to the need for proficiency in general PN skills. This tutorial focuses on the daily management of adult hospitalized patients already receiving PN and reviews the following topics: (1) PN basics, including the determination of energy and volume requirements; (2) PN macronutrient content (protein, dextrose, and intravenous fat emulsion); (3) PN micronutrient content (electrolytes, minerals, vitamins, and trace elements); (4) alteration of PN for special situations, such as obesity, hyperglycemia, hypertriglyceridemia, refeeding, and hepatic/renal disease; (5) daily monitoring and adjustment of PN formula; and (6) PN‐related complications (PN‐associated liver disease and catheter‐related complications).